A decomposition analysis of the German gender pension gap - Carsten Hänisch; Jonas Klos (Albert-Ludwigs-Universität Freiburg, Wilfried-Guth-Stiftungsprofessur für Ordnungs- und Wettbewerbspolitik, 2014)
This paper discusses the gap in own old-age incomes of men and women and explores the causes for these differences by means of decomposition methods using German micro-data of the survey 'Alterssicherung in Deutschland' (ASID). The Gender Pension Gap has decreased but still amounts to about 60% as of 2007. We find that this gap is mainly explained by differences in labor market experience and education. The gap is especially high at the lower end of the pension income distribution. The contribution of differing labor market experiences to the explained gap is particularly pronounced for retires with low pensions.
Keywords: 330; Social Security; Public Pensions; Pension Gap; Decomposition